2020
DOI: 10.1101/2020.09.30.20203315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widening the gap: greater racial and ethnic disparities in COVID-19 burden after accounting for missing race/ethnicity data

Abstract: Black, Hispanic, and Indigenous persons in the United States have an increased risk of SARS-CoV-2 infection and death from COVID-19, due to persistent social inequities. The magnitude of the disparity is unclear, however, because race/ethnicity information is often missing in surveillance data. In this study, we quantified the burden of SARS-CoV-2 infection, hospitalization, and case fatality rates in an urban county by racial/ethnic group using combined race/ethnicity imputation and quantitative bias-adjustme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 9 publications
2
44
1
Order By: Relevance
“…Considering our findings substantiate reports of increased COVID-19 burden among ethnic minority groups in other countries, it is concerning that information on ethnicity is often not collected in routine surveillance systems in many countries(29). This results in these important differences in disease burden being concealed within the data, hindering the ability to set up targeted initiatives to reach particularly vulnerable populations.…”
Section: Discussionsupporting
confidence: 86%
“…Considering our findings substantiate reports of increased COVID-19 burden among ethnic minority groups in other countries, it is concerning that information on ethnicity is often not collected in routine surveillance systems in many countries(29). This results in these important differences in disease burden being concealed within the data, hindering the ability to set up targeted initiatives to reach particularly vulnerable populations.…”
Section: Discussionsupporting
confidence: 86%
“…The limitations of this study include the use of administrative data and self-reported racial designations; approximately 22% of patients in our study belonged to an unknown racial category, which may limit our ability to draw inferences [ 9 , 10 ]. Further, our documentation of telehealth early in the pandemic was unable to distinguish telephonic and video visits, which may vary across racial and age groups [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Complicating the evaluations of these disparities is the reliance on medical record reporting of race/ethnicity. A recent epidemiological analysis estimates that due to inherent biases of medical record documentation and missing data, complete case analyses are likely underestimating the magnitude of the racial and ethnic disparities seen in most reporting thus far, and at a minimum suggest using quantitative bias analysis methods that account for unequal and non-random missingness [ 84 ].…”
Section: Sars-cov2 Infection In Special Pediatric Nephrology Populationsmentioning
confidence: 99%